2019
DOI: 10.1038/s41598-019-51553-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial random noise stimulation (tRNS): a wide range of frequencies is needed for increasing cortical excitability

Abstract: Transcranial random noise stimulation (tRNS) is a recent neuromodulation protocol. The high-frequency band (hf-tRNS) has shown to be the most effective in enhancing neural excitability. The frequency band of hf-tRNS typically spans from 100 to 640 Hz. Here we asked whether both the lower and the higher half of the high-frequency band are needed for increasing neural excitability. Three frequency ranges (100–400 Hz, 400–700 Hz, 100–700 Hz) and Sham conditions were delivered for 10 minutes at an intensity of 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 46 publications
(64 reference statements)
1
61
0
Order By: Relevance
“… 11 15 Along the same lines, Thompson et al., 16 Clavagnier et al., 17 and Moret et al. 18 showed that contrast sensitivity improvements for the amblyopic could be made in adults with amblyopia using repetitive transcranial magnetic stimulation (rTMS) and high-frequency transcranial electrical stimulation. In an animal study, Castano-Castano et al.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“… 11 15 Along the same lines, Thompson et al., 16 Clavagnier et al., 17 and Moret et al. 18 showed that contrast sensitivity improvements for the amblyopic could be made in adults with amblyopia using repetitive transcranial magnetic stimulation (rTMS) and high-frequency transcranial electrical stimulation. In an animal study, Castano-Castano et al.…”
mentioning
confidence: 91%
“…These studies report an improvement in both binocular and monocular functions in patients with strabismic, as well as anisometropic, amblyopia after therapy designed to reduce suppression. [11][12][13][14][15] Along the same lines, Thompson et al, 16 Clavagnier et al, 17 and Moret et al 18 showed that contrast sensitivity improvements for the amblyopic could be made in adults with amblyopia using repetitive transcranial magnetic stimulation (rTMS) and high-frequency transcranial electrical stimulation. In an animal study, Castano-Castano et al 19 found that amblyopic rats can produced an almost full recovery in visual acuity after eight sessions of anodal transcranial direct current stimulation on the visual cortex.…”
mentioning
confidence: 99%
“…The plasticity-inducing effect of iTBS was absent in PD patients, but tRNS reduced cortical excitability as compared to pre-stimulation baseline, which is in contrast to the results on healthy subjects (Stephani et al, 2011). Recently, Moret et al (2019) has noted that, for inducing a significant and persistent increase in cortical excitability, a large amount of noise with a wide range of frequencies (100-700 Hz) is needed.…”
Section: Transcranial Random Noise Stimulationmentioning
confidence: 67%
“…Until now, a consistent change in corticomotor excitability measurements has mainly been demonstrated after prolonged tRNS delivery, an effect that has been hypothesized to reflect long-lasting neuroplastic changes (Terney et al 2008;Chaieb et al 2011Chaieb et al , 2015Abe et al 2019;Moret et al 2019). However, neuroplastic changes are unlikely to have driven the acute tRNS effects in our study since tRNS conditions were always interleaved with no-noise baseline or other control conditions, thereby minimizing the influence of long-term excitability changes.…”
Section: Alternative Accounts Of the Observed Acute Trns-induced Noismentioning
confidence: 71%